Lower proportions of CD4+CD25high and CD4+FoxP3, but not CD4+CD25+CD127low FoxP3+T cell levels in children with autoimmune thyroid diseases. (May 2013) - Bossowski, A.; Moniuszko, M.; Dąbrowska, M.; Sawicka, B.; Rusak, M.; Jeznach, M.; Wójtowicz, J.; Bodzenta-Lukaszyk, A.; Bossowska, A.
<x xml:space="preserve">Abstract</x> The essence of autoimmune thyroid disease (AITD) is loss of tolerance of own tissues caused by malfunction of T lymphocytes, which affects the production of antibodies reacting with particular cell structures and tissues. Foxp3+ regulatory T cells (Tregs) take part in the regulation of immune response and play a leading role in developing immune tolerance through active suppression. The aim of the study was to estimate the expression of CD4+CD25high, CD4+CD25+CD127lowFoxP3+ and CD4+ FoxP3 T cells in patients with Graves' disease (GD) (n = 24, median age 15.5 years), in patients with Hashimoto's thyroiditis (HT) (n = 30, median age 15 years) in comparison with sex- and age-matched healthy control subjects (n = 30, median age 15 years). Polychromatic flow cytometry using a FACSCalibur (BD Biosciences) cytometer was applied to delineate T regulatory cell populations. In untreated patients with Graves' disease and HT we observed a significant decrease in CD4+FoxP3 (p < 0.001, p < 0.01) and CD4+CD25high (p < 0.016, p < 0.048) T lymphocytes as compared to the healthy control subjects. After 6–12 months of L-thyroxine therapy in HT cases these phenotypes of Tregs were normalized, yet no such changes were observed during GD therapy. The analysis of CD4+CD25+CD127lowFoxP3+T cells in the peripheral blood revealed comparable percentages of these cells in patients with thyroid autoimmune diseases to the controls. We conclude that the reduction number of Tregs with CD4+CD25high and CD4+FoxP3 phenotype suggests their role in initiation and development of autoimmune process in thyroid disorders.